aubergine encodes a Drosophila polar granule component required for pole cell formation and related to eIF2C. - Harris, A.N.; Macdonald, P.M. (Development, 2001)
In Drosophila oocytes, activation of Oskar translation from a transcript localized to the posterior pole is an essential step in the organization of the pole plasm, specialized cytoplasm that contains germline and abdominal body patterning determinants. Oskar is a component of polar granules, large particles associated with the pole plasm and the germline precursor pole cells of the embryo. aubergine mutants fail to translate oskar mRNA efficiently and are thus defective in posterior body patterning and pole cell formation. We have found that Aubergine protein is related to eukaryotic translation initiation factor 2C and suggest how it may activate translation. In addition, we found that Aubergine was recruited to the posterior pole in a vas-dependent manner and is itself a polar granule component. Consistent with its presence in these structures, Aubergine is required for pole cell formation independently of its initial role in oskar translation. Unlike two other known polar granule components, Vasa and Oskar, Aubergine remains cytoplasmic after pole cell formation, suggesting that the roles of these proteins diverge during embryogenesis.